From Reader-Response Criticism to Reading Animation: Theoretical Considerations for a Literary Reading Animation Project in Unconventional Settings - Higuera Guarín, Gladys Yaneth (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The present article aims at exploring the way in which reader-response criticism becomes the basis for understanding the importance of reading promotion in at-risk communities. This reflection provides the theoretical support for the development of a reading animation project with the interns of El Olivo prison in Santa Rosa de Viterbo, Colombia, using strategies such as reading animation formats by Beatriz Robledo and reading categories by Sarah Hirschman